FINANCIAL PERFORMANCE AND TRADING ACTIVITY AS DETERMINANTS OF STOCK PRICES IN ASEAN RETAIL FIRMS - Saputra, Darman; Julia; Pratama, Sari Indra (Universitas Putera Batam, 2025)
Obtaining cash from the general public through the stock market is one of the ways that businesses may participate in the capital market. In addition to generating prospects for stock exchanges in international markets, the capital markets in the ASEAN area provide new opportunities to investors in the nations that make up the ASEAN region. Specifically, the purpose of this study is to investigate the impact that fundamental considerations and systematic risk have on the values of shares that are traded on the Asean Stock Exchange. Purposive sampling is the procedure that is utilized in the sampling methodology. The population of this study consists of all of the retail sector firms that are listed on the ASEANStock Exchange. There are 121 companies in the population, and 23 companies are included in the sample. The findings of the research indicate that the return on assets has a negative impact on stock prices, earnings per share does not have any impact on stock prices, the debt to equity ratio does not have any impact on stock prices, the price earnings ratio has a positive impact on stock prices, and the volume of stock trading has no impact on stock prices. These findings pertain to the stock prices of companies operating in the retail sector.